2017
DOI: 10.1016/j.ultrasmedbio.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Coronary Artery Disease Using Myocardial Elastography with Diverging Wave Imaging: Validation against Myocardial Perfusion Imaging and Coronary Angiography

Abstract: Myocardial elastography (ME) is an ultrasound-based technique that can image 2-D myocardial strains. The objectives of this study were to show that 2-D myocardial strains can be imaged with diverging wave imaging and are different in average between normal and coronary artery disease (CAD) patients. In this study, 66 patients with symptoms of CAD were imaged with ME prior to a nuclear stress test or an invasive coronary angiography. Radial cumulative strains were estimated in all patients. The end-systolic rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Although previous referenced studies using strain or strain rate imaging to identify MI patients did not have the same level of diagnostic resolution, they were performed in patients in the clinic (Delgado et al 2008;Edvardsen et al 2002;Eek et al 2010;Gjesdal et al 2009;Gjesdal et al 2009;Grenne et al 2010;Zhang et al 2005). While ME for MI diagnosis needs to be validated in a patient model, a previous study using ME to diagnose 66 patients with suspected CAD demonstrated that ME was capable of localizing ischemia to a specific perfusion territory (Grondin et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous referenced studies using strain or strain rate imaging to identify MI patients did not have the same level of diagnostic resolution, they were performed in patients in the clinic (Delgado et al 2008;Edvardsen et al 2002;Eek et al 2010;Gjesdal et al 2009;Gjesdal et al 2009;Grenne et al 2010;Zhang et al 2005). While ME for MI diagnosis needs to be validated in a patient model, a previous study using ME to diagnose 66 patients with suspected CAD demonstrated that ME was capable of localizing ischemia to a specific perfusion territory (Grondin et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although ME does not explicitly measure elastic properties of the myocardium, the strain imaging technique is based on the signal processing approach detailed in the first publication defining elastography (Ophir et al 1991). Previous applications have included ablation monitoring in canines and humans (Bunting et al 2018;Grondin et al 2015), tracking the progression of acute ischemia in an open-chest canine model (Lee et al 2011), and imaging suspected coronary artery disease (CAD) patients (Grondin et al 2017). ME has also been used to image MI in a murine model (Luo et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Reconstruction of radiofrequency (RF) signals for all three transmit strategies was performed with a delay-and-sum parallel beamformer as described in previous reports (Grondin et al 2017c;Sayseng et al 2018). The polar reconstruction grid featured a 90° field-of-view with 180 lines, 77 μm axial sampling, and 14 cm depth.…”
Section: Description Of Transmit Strategiesmentioning
confidence: 99%
“…Strain imaging has proven to be a useful tool in assessing myocardial health (D'hooge et al 2000, Abraham et al 2007, Dandel et al 2009, Smiseth et al 2016. Myocardial Elastography (Konofagou et al 2002, Lee et al 2007, a cardiac strain imaging technique developed by our group, is the particular focus of this study; its applications include tracking ischemia progression in canines (Lee et al 2011), lesion monitoring during RF ablation in canines and humans (Grondin et al 2015, Bunting et al 2018, and quantitatively differentiating ischemic from normal patients as validated by nuclear imaging and angiography (Grondin et al 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…ME has been theoretically validated with a 3D finite-element model based on a normal and ischemic canine left ventricle, and has been experimentally validated in vivo with tagged magnetic resonance imaging (tMRI) of a healthy human volunteer [6]. The capabilities of ME include localization of infarcts in a mice model [7], monitoring of ischemia progression in a canine model [8], monitoring of RF ablation therapy in both canines and human patients with atrial fibrillation [9], and differentiating ischemic patients from healthy individuals [10]. This study is focused on the application of ME to estimate radial and circumferential cardiac strain in the short-axis view.…”
Section: Introductionmentioning
confidence: 99%